Seesaw system: modeling and analysis / Johari Mohamad Tahar - Mohamad Tahar, Johari (1998)
The seesaw system is one example of an unstable system and is a classical problem in control theory. Many different approaches in construction and control methodologies have been studied by different researchere in order to solve this problem. It has been used many tunes as a model on how to control an unstabilize system. The main task of this project is to study the method or technique that allows a cart on the seesaw to be balanced in less than 5 seconds and maintain the balance. The cart is controlled by a d.c motor and moves along the pendulum track on the seesaw. A computer is used to control the position of the cart and the angular position of the seesaw. This project apply the optimal control theory to maintains the seesaw to remains at horizontal position or at stable state.